Some remarks on article 29 of the Labor Code in the light of the Act dated 13 May 2016 amending the Act – Labor Code - Wączek, Bartosz (The Opole Studies in Administration and Law, 2019)
The aim of this article is to present practical difficulties and their solutions and also to illustrate effects of the introduced amendment to Art. 29 § 2 of the Act of June 26, 1974 of Labour Code. The author shows how this regulation was shaped in previous amendments in his attempt to answer how the finally introduced amendments have improved the situation of employees. Consequently, the aim of the article is to present the benefits resulting from this change, but also the risks arising upon introduction of the latest amendment. The author considers the question whether the procedure, however simple from the point of view of the legislative technique, is not an unfortunate attempt to patch the legal gap, which is often the subject of abuse. In the text, the author also wonders how the amended provision affects the situation of people starting work and what it alters in the case of people who have been in the labour market for years.